Comparison of revascularization with conservative medical treatment in maintenance dialysis patient with coronary artery disease: a systemic review and meta-analysis - Zheng, Ling; Wang, Xiang; Zhong, Yu-cheng (Frontiers in Cardiovascular Medicine, 2023)
Background The primary cause of death among maintenance dialysis patients is coronary artery disease (CAD). However, the best treatment plan has not yet been identified. Methods The relevant articles were retrieved from various online databases and references from their inception to October 12, 2022. The studies that compared revascularization [percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG)] with medical treatment (MT) among maintenance dialysis patients with CAD were selected. The outcomes evaluated were long-term (with a follow-up of at least 1 year) all-cause mortality, long-term cardiac mortality, and the incidence rate of bleeding events. Bleeding events are defined according to TIMI hemorrhage criteria: (1) major hemorrhage, intracranial hemorrhage or clinically visible hemorrhage (including imaging diagnosis) with decrease of hemoglobin concentration ≥5 g/dl; (2) minor hemorrhage, clinically visible bleeding (including imaging diagnosis) with a drop in hemoglobin of 3–5 g/dl; (3) minimal hemorrhage, clinically visible bleeding with hemoglobin drop <3 g/dl. In addition, revascularization strategy, CAD type, and the number of diseased vessels were considered in subgroup analyses. Results A total of eight studies with 1,685 patients were selected for this meta-analysis. The current findings suggested that revascularization was associated with low long-term all-cause mortality and long-term cardiac mortality but a similar incidence rate of bleeding events compared to MT. However, subgroup analyses indicated that PCI is linked to decreased long-term all-cause mortality compared to MT but CABG did not significantly differ from MT in terms of long-term all-cause mortality. Revascularization also showed lower long-term all-cause mortality compared to MT among patients with stable CAD, single-vessel disease, and multivessel disease but did not reduce long-term all-cause mortality among patients with ACS. Conclusion Long-term all-cause mortality and long-term cardiac mortality were reduced by revascularization in comparison to MT alone in patients undergoing dialysis. Larger randomized studies are needed to confirm the conclusion of this meta-analysis.